An Older and Exceptionally Large Adult Specimen of Tyrannosaurus rex. Issue 4 (8th April 2019) - Persons, W. Scott; Currie, Philip J.; Erickson, Gregory M.
ABSTRACT: Here we describe an extremely large and relatively complete (roughly 65%) skeleton of Tyrannosaurus rex (RSM P2523.8). Multiple measurements (including those of the skull, hip, and limbs) show that RSM P2523.8 was a robust individual with an estimated body mass exceeding all other known T. rex specimens and representatives of all other gigantic terrestrial theropods. Histological sampling of the fibula confirms that RSM P2523.8 is skeletally mature. The prevalence of incompletely coossified elements contradicts previous assertions that such unfused elements can be taken as indicators of somatic immaturity. As an extreme example of both ontogenetic maturity and osteological robustness, RSM P2523.8 offers support for prior hypotheses that a sampling bias occurs throughout the Dinosauria, making it likely that most taxa grew to significantly greater size than current known specimens indicate. Anat Rec, 303:656–672, 2020. © 2019 Wiley Periodicals, Inc.